Lighting of housing, administrative and temple complexes in the city of Tara, Omsk Oblast, Russia, in the 17–19th centuries - Tataurov S.F. (Вестник археологии, антропологии и этнографии, 2019)
This study reveals the problem of lighting of buildings — domestic, administrative and religious — in the city of Tara during the 17–19th centuries. At night, especially in the winter, many economic activities took place indoors, making adequate lighting of interiors of dwellings a priority. In the evenings, women spun, wove, and processed the products of agriculture and foraging. Men carved wooden utensils, made footwear and engaged in other crafts. This article describes the window as one of the key structural elements of the dwelling and discusses the process of replacing mica windows with glass in the 18th and 19th centuries. It illustrates the range of lights and candlesticks recovered during archaeological excavations. The social significance of lighting devices for the population of a Russian Siberian city is shown. In the city of Tara provision of lighting fell into three categories. The system of lighting in Tarsky churches was the most difficult — large windows were made to maximise light, often at the expense of warmth, and special lamps and numerous icon holders to candles were used. However, these devices were used only on church holy days, and on weekdays there was only natural light in the churches. Significant funds were spent by the Tara administration on lighting state buildings — military and clerk's huts, an arsenal, a treasury, etc. Excavation findings show that candlesticks were used to hold candles. The wood splinter was the main source of light in houses of working people and petty bourgeoises, but findings of the combined illuminations with nests under candles indicate that on holy days residents used the corresponding holy day lighting. The archaeological findings associated with the lighting of housing, administrative and religious complexes, are some of the most indicative markers of innovations in the city in the fields of construction and architecture, living conditions and life. The study of this subject is also relevant to trade relations, because a considerable number of the objects associated with lighting are imported.